FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN KONSUMEN MELAKUKAN PEMBELIAN MAKANAN MELALUI MEDIA SOSIAL - Aylinna Ongsano; Michael Ricky Sondak (Universitas Bunda Mulia, 2017)
Sophistication of technology is now increasingly, people becomes easier to access any information just by using internet. This evolution is called globalization. Now globalization makes Indonesian people tend to likes instant and practical things. Internet users in Indonesia is now increasing and most are social media active users. This makes Indonesia have a good prospects to do online business. The purpose of this study is to find out the factors that influence consumer’s decision for purchase online food and to determine the most dominant factor in consumer’s decision for purchasing online food. Population in this research is all Indonesia people who already experienced online transaction. Meanwhile, sample of this research is 73 consumers who have already purchased online food. Moreover, the technique of data collection in this study is through questionnaires distribution method and the questionnaires is using Likert scale instrument. Furthermore, the researcher process the data using SPSS with Exploratory Factor Analysis to obtain significant conclusions based on these research. Based on the hypothesis that has been calculated using the SPSS, the results are there are five factors that influence consumer’s decision for purchasing food through social media and the most dominant factor is life style, because it has the most high eigen value.Keywords: Globalization, Social Media, Online Business, Exploratory Factor Analysis